Pengembangan Bahan Ajar “Nilai Karakter Tokoh Pandawa” untuk Sekolah Dasar - Catur Arib Akbar Arrofiif; Retno Winarni; Joko Daryanto (Universitas Sebelas Maret, 2026)
This study aims to identify the characteristics of teaching materials needed inlearning Javanese, develop and produce teaching materials